2022
DOI: 10.1002/ddr.21929
|View full text |Cite
|
Sign up to set email alerts
|

Astragaloside IV alleviates oxidative stress‑related damage via inhibiting NLRP3 inflammasome in a MAPK signaling dependent pathway in human lens epithelial cells

Abstract: Oxidative stress alters cellular microenvironment, facilitating cell apoptosis and inflammatory response, and oxidation of lens constituents may ultimately result in cataracts. Astragaloside IV (AS-IV) exhibits a variety of pharmacological activities, such as antioxidative and anti-inflammatory activity via regulating various signaling pathways. However, the effect of AS-IV on lens epithelial cells and its potential therapeutic role in cataracts remained to be investigated. In this study, AS-IV prevented H 2 O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Conversely, Sanguinarine was reported to upregulate JNK and p38 signaling leading to increased lens epithelial cell apoptosis [205]. Recently, two further in vitro studies reported an amelioration of oxidative stress-related damage by MAPK suppression through regulation of the NLRP3 inflammasome [206] or through as of yet unelucidated functions of the flavonoid Diosmetin from chrysanthemum, that is used in traditional Chinese medicine [207]. Another recent study has similarly reported corroborating results, with p38 and ERK phosphorylation downregulation also being associated with decreased apoptosis via another proxy (TRIM22) [208].…”
Section: Mapk In Other Ocular Pathophysiologiesmentioning
confidence: 99%
“…Conversely, Sanguinarine was reported to upregulate JNK and p38 signaling leading to increased lens epithelial cell apoptosis [205]. Recently, two further in vitro studies reported an amelioration of oxidative stress-related damage by MAPK suppression through regulation of the NLRP3 inflammasome [206] or through as of yet unelucidated functions of the flavonoid Diosmetin from chrysanthemum, that is used in traditional Chinese medicine [207]. Another recent study has similarly reported corroborating results, with p38 and ERK phosphorylation downregulation also being associated with decreased apoptosis via another proxy (TRIM22) [208].…”
Section: Mapk In Other Ocular Pathophysiologiesmentioning
confidence: 99%
“…Astragaloside IV (AST, Figure 1A), a cycloartane-type triterpene glycoside chemical, is one of the major compounds extracted from Astragalus membranaceus (Zhang et al, 2020). In LECs, AST could ameliorate oxidative stress-induced damage through the inhibition of NLRP3 inflammasomes via regulating MAPK signaling pathway (Xiao et al, 2022). It is revealed that AST alleviates TGF-β-induced cardiac fibrosis, pulmonary fibrosis, hepatic fibrosis and renal fibrosis (Du et al, 2018;Qian et al, 2018;Singh et al, 2021;Wei et al, 2020), indicating the anti-fibrosis effects of AST.…”
Section: Astragaloside IV Inhibits the Growth Of Lens Epithelial Cellsmentioning
confidence: 99%
“…Astragaloside IV (AS-IV) is a saponin derived from a commonly used Chinese herb, Astragalus membranaceus Bge. AS-IV is known to possess a wide range of pharmacological activities, including, cardioprotective [7][8][9], anti-inflammatory [10,11], anti-oxidant [12][13][14], and anti-cancer properties [15][16][17]. Moreover, AS-IV is well established as a promoter of osteogenesis [18][19][20][21], and inhibitor of osteoclastogenesis [22].…”
Section: Introductionmentioning
confidence: 99%